Polygon Area Board Game for Building Thinking Skills in Area Conservation and Measurement - Karlimah, Karlimah; Lidinillah, Dindin Abdul Muiz; Supriadi, Supriadi; Apriani, Ika Fitri; Insani, Sofi Mutiara (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
This study aimed to develop a board game to enhance fifth-grade students' understanding of area concepts and the law of conservation of area in polygons. The research employed the ADDIE model, covering analysis, design, development, implementation, and evaluation stages. Expert validation and classroom trials were conducted to assess validity, practicality, and effectiveness. The results showed that the board game achieved a validity score of 89% (very feasible) and improved students' test performance by 23%. Students exhibited high engagement and active participation during learning activities. The study highlights the importance of integrating design elements such as layout, color, and illustration to support conceptual understanding. It concludes that well-designed board games can effectively foster critical thinking and motivation in elementary mathematics learning.